Modelling of the multi-chamber oscillating water column in regular waves at model scale. (October 2017) - Shalby, Mohammad; Walker, Paul; Dorrell, David G.
Abstract: This paper studies the reliability of numerical models used for estimating multi-chamber oscillating water column (MC-OWC) response in the time-domain. The model for the internal water surface level and instantaneous pressure inside the chamber at regular waves conditions using a hybrid system of hydrodynamic and thermodynamic rigid piston models without power take-off. Reliability is assessed using experimental data obtained from a wave tank used in the model concept validation. The results show the method could be extended to describe the hydrodynamics of the MC-OWC in regular and irregular wave conditions.